Social Forestry for Economic, Social, and Environmental Sustainability: A Bibliometric Analysis - Westi Utami (Jurnal Ilmu Lingkungan, 2026)
Social forestry can be defined as a strategy for resolving forest tenure conflicts, reducing poverty, and maintaining the sustainability of forest ecosystems/environments. Nevertheless, studies that address the subject of social forestry literature reviews are extremely scarce. This condition has the potential to impede a comprehensive understanding and limit prospects for future social forestry research initiatives. The present study aims to analyse the role of social forestry in achieving social, economic and environmental sustainability. The present study utilised the Scopus database, which encompasses 429 manuscripts, and employed R-Studio and Vosviewer for the purpose of data analysis. The research findings indicate that Forest and Society is the most productive publisher. The three institutions with the highest number of publications are Hasanuddin University, Gadjah Mada University, and Bogor Agricultural University. This analysis demonstrates that Indonesia is the nation with the most prolific number of publications in the domain of social forestry. Social forestry studies have undergone substantial development. In the 2000s, the majority of studies were related to the sub-themes of deforestation, biomass, and participation. Concurrently, in 2010, the study sub-themes exhibited a stronger correlation with livelihoods and community forestry. In the 2020s, the focus shifted towards conservation, climate change, and sustainable forest management. The implementation of social forestry is encumbered by a number of challenges and problems. In certain regions, the implementation of social forestry initiatives has successfully addressed tenurial conflicts, thereby ensuring legal clarity with respect to land tenure. Nevertheless, the implementation of this policy has not yet resulted in significant improvements to people's lives or achieved environmental sustainability, including in terms of forest ecosystems. It is evident that inadequate mentoring, inadequate funding, limited community participation, and limited structured monitoring and evaluation of social forestry policies have collectively impeded this policy from achieving the desired levels of social, economic, and environmental sustainability.